2022
DOI: 10.3390/app12052468
|View full text |Cite
|
Sign up to set email alerts
|

MIC-1 Antlerogenic Stem Cells Homogenate from Cervus elaphus Accelerate Corneal Burn Reepithelization in Rabbits

Abstract: Deer antler is the only mammalian organ that can fully grow back once lost from its pedicle. Antler regeneration is a stem cell-based process. Therefore, antlers probably offer the most pertinent model for studying organ regeneration in mammals. Evaluation of the effect of deer antler stem cells on the healing of superficial and deep rabbit corneal wounds was performed. Thirty-six New Zealeand White rabbits were used in this study in superficial and deep denaturation models, and corneal erosion was performed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The results showed that ASC treatment had a positive effect on corneal wound healing and attenuated or prevented the occurrence of side effects such as blepharospasm, vascular penetration, corneal injury, and conjunctival sac outflow [ 80 ]. In a rabbit model of a superficial and deep corneal wound, topical application of ASC homogenate was effective in healing the corneal wound after exposure to n-heptanol [ 81 ]. Topical application of ASCs resulted in a smaller area of lesion damage and significantly improved corneal clarity compared to controls [ 81 ].…”
Section: Medical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that ASC treatment had a positive effect on corneal wound healing and attenuated or prevented the occurrence of side effects such as blepharospasm, vascular penetration, corneal injury, and conjunctival sac outflow [ 80 ]. In a rabbit model of a superficial and deep corneal wound, topical application of ASC homogenate was effective in healing the corneal wound after exposure to n-heptanol [ 81 ]. Topical application of ASCs resulted in a smaller area of lesion damage and significantly improved corneal clarity compared to controls [ 81 ].…”
Section: Medical Applicationsmentioning
confidence: 99%
“…In a rabbit model of a superficial and deep corneal wound, topical application of ASC homogenate was effective in healing the corneal wound after exposure to n-heptanol [ 81 ]. Topical application of ASCs resulted in a smaller area of lesion damage and significantly improved corneal clarity compared to controls [ 81 ]. Studies have shown that vesicles secreted in ASC-conditioned media can act as paracrine mediators to regulate the expression of wingless-related integration site (Wnt)-3a, Wnt-10b, and lymphoid-enhancing-binding factor 1 and promote tissue regeneration [ 82 ].…”
Section: Medical Applicationsmentioning
confidence: 99%